Study on Flood Season Staging of Different Stationsin Xijiang River Based on Fuzzy Set Analysis - WANG Yuhu; WANG Baohua; FAN Hongxia; HOU Guibing; LI Yuanyuan (Renmin Zhujiang)
The flood of the Xijiang River basin is formed by the heavy rain, with obvious seasonalvariation law, and the study of the flood season staging is of great significance to optimize theoperation of the reservoir and coordinate the contradiction between flood control and benefitpromotion. This paper studies the flood season staging of different stations in Xijiang River bythe fuzzy set analysis method, and comprehensively determines the stages of the flood season ofdifferent stations as follows: for Wuxuan station, the pre-flood period is from April 1 to May 26,the main flood period is from May 27 to August 15, and the post-flood period is from August 16 toOctober 31; for Dahuangjiangkou station, the pre-flood period is from April 1 to June 3, the mainflood period is from June 4 to August 14, and the post-flood period is from August 15 to October31; while for Wuzhou station: the pre-flood period is from April 1 to June 6, the main floodperiod is from June 7 to August 30, and the post-flood period is from August 31 to October 31. Theresults show that the period of the flood season staging of different stations in Xijiang isdifferent, and the period of flood season staging set by the fuzzy set analysis method isconsistent with that obtained from the actual flood control experience and the actual situation ofthe stations, which can provide the technical reference for the flood control & drought relief andthe optimal scheduling of the reservoir group.